Bioresorbable thermo-responsible injectable hydrogel for temporary tract embolization in interventional radiology - Tan, Pei Leng (2016)
Liver biopsy involves the needle extraction of a small suspicious lesion liver tissue for diagnosis which leaves behind a tract cavity in the liver site. In more fatal complications it will result in severe haemorrhage and as such tract embolization is commonly employed as a post biopsy procedure to minimize the occurrence of haemorrhage or for haemostatic purposes in cases of haemorrhage. Gelfoam sponge is the only available biodegradable embolic agent used for embolization. However, it is associated with major limitations such as non-targeted occlusion, complicated preparation and application of the Gelfoam sponge. A novel biodegradable injectable polymer, Pluronic F127, was proposed as a substitute for Gelfoam to enhance the ease of embolization. It was hypothesised that the thermal responsive mechanism of Pluronic F127 can actuate the device at physiological temperature upon contact with blood and embolize tract cavity. Hence the rheological characteristics of increasing amount of Pluronic F127 were studied to determine the optimal concentration for such application. Following which the effects of increasing concentrations of radiopaque mediums on mechanical properties of the Pluronic F127 polymer were explored to determine an optimal formulation of 19% Pluronic F127 with 30% barium sulphate for a high storage modulus embolic device. A simple and effective tilt method was conducted under different heating condition to substantiate the thermal responsivity mechanism of the device. The device was injected into flow model tract cavities to study the in-vitro viability of Pluronic F127 polymer as an injectable embolic device. The in-vitro flow test exhibited a 100% occlusion instantaneously with full dissolution after 23 minutes. These results have demonstrated the potential on the use of injectable thermal-responsive Pluronic polymer as a future bioresorbable injectable hydrogel for temporary tract embolization.